Compound sulfamethoxazole for pediatric pertussis: a retrospective cohort study in a region with high macrolide resistance - Li, Lin; Xie, Taohong; Xiao, Liu; Zhong, Ying; Wang, Mingying; Su, Yaping (Frontiers in Pediatrics, 2025)
BackgroundIn recent years, the incidence of pertussis has been increasing globally. The high prevalence of macrolide-resistant strains has led to a significant rise in both pertussis cases and associated mortality.ObjectiveThis retrospective study aimed to evaluate the clinical effectiveness and safety of compound sulfamethoxazole (SMZco) vs. macrolides in pediatric pertussis treatment under real-world clinical conditions, providing evidence for its clinical application.MethodsPatients were divided into macrolide and SMZco groups based on treatment regimens. Comparative analyses included overall treatment effectiveness, duration of nocturnal coughing, paroxysmal coughing, post-tussive vomiting, hospitalization length, and adverse drug reactions.ResultsThe macrolide group (n = 23) showed 3 markedly effective, 8 effective, and 12 ineffective cases (total effectiveness rate 47.8%). The SMZco group (n = 79) demonstrated 26 markedly effective, 38 effective, and 15 ineffective cases (total effectiveness rate 81.0%), with significantly superior effectiveness vs. macrolides (P < 0.05). The SMZco group exhibited statistically significant reductions in hospitalization duration (P < 0.05), paroxysmal coughing (P < 0.05), post-tussive vomiting (P < 0.05), and nocturnal coughing (P < 0.05). Gastrointestinal adverse events occurred in 8 macrolide-treated patients vs. 6 SMZco-treated patients (P < 0.05). Rash was observed in 12 SMZco-treated cases but none in the macrolide group (P < 0.05).ConclusionSMZco significantly improves treatment effectiveness, shortens symptom duration and hospitalization, and reduces economic burden in pediatric pertussis. These findings position SMZco as an effective and safe alternative, particularly in regions with high macrolide resistance.